Pengaruh Komunikasi Interpersonal Terhadap Burnout Pada Pegawai Yayasan Medan Plus - Ayurizkina, Naputri; Syafrizaldi, Syafrizaldi (Tabularasa: Jurnal Ilmiah Magister Psikologi, 2025)
The purpose of this study was to determine and empirically test the effect of Interpersonal Communication on Burnout in Medan Plus Foundation Employees. The method used was a quantitative method with a population of 63 people. The sampling technique used was total sampling, so the sample numbered 63 people. The data analysis technique used was a simple regression analysis. Based on the results of the simple regression analysis, the results of the t count (4.312) and t table (1.669) were obtained, which means that t table t count, namely 4.312 1.669 so that the results showed that there was an influence between interpersonal communication and the tendency to burnout. Furthermore, the coefficient of determination (r2) of the relationship between the independent variable and the dependent variable is r2 = 0.234. This shows that Interpersonal Communication has a contribution to the Tendency of Burnout by 23.4%. Interpersonal Communication is classified as low with a hypothetical mean value of 85 and an empirical mean of 71.90. Furthermore, the Tendency of Burnout obtained high results with a hypothetical value of 50 and an empirical value of 70.52.